Efektivitas Flipped Classroom Terhadap Motivasi Belajar Dan Pemahaman di SMKN 1 Kamal - Karimah; Tri Eka Silver, Soesiana; Huda, Nuril (Penerbit STKIP PGRI Bangkalan, 2024)
In this research, to determine the effectiveness of the flipped classroom on students' understanding of mathematics in class X visual communication design at SMKN 1 Kamal. Researchers hope that the application of the flipped classroom-based learning model in mathematics lessons will become an alternative for developing students' creative potential, fostering a sense of responsibility, and increasing students' motivation and understanding. Researchers used a sample of class X Visual Communication Design of 28 students at SMKN 1 Kamal consisting of 19 male and 9 female students. Based on the pretest analysis (before being given treatment) obtained from the questions of understanding with a minimum score of 15, a maximum score of 95, an average of 60.00, while a posttest (after being given treatment) obtained a minimum score of 60, a maximum score of 95, the average -rat 76.96 So it can be concluded that there was an increase in the minimum, maximum and average scores of students in understanding after being given treatment. Based on the output above, the value obtained for the flipped classroom model on understanding is 0.000<0.05, which shows that there is a significant difference so that the application of the flipped classroom can increase students' understanding of mathematics material in class X visual communication design at SMKN1 Kamal